Kilka uwag o ochronie życia poczętego w kontekście projektowanych zmian kodeksu karnego - Kokot, Rajnhardt; Jasińska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the issues of criminallaw protection of life and health of the conceived child de lege lata and de lege ferenda. It brings closer the current rules of criminal responsibility for the attacks directed at this good and discusses the state of dogmatic theology and jurisprudence in this area. It presents the most important controversies at the level of science of law and jurisprudence and dilemmas of interpretation. The leading theme of this paper is the presentation and analysis of the changes to the Cryminal Code proposed by the Codification Commission in the draft of 2013. It draws attention to their wide scope and substantive significance. They represent modifications of systemic character and of fundamental significance to the very idea of protection of human life.
Keywords: życie; prawo karne; ochrona; dziecko poczęte; aborcja; ciąża; lekarz; nowelizacja kodeksu karnego